Eletro-oxidação de metanol e etanol sobre catalisadores suportados de 'PD''AU' - Abreu, Thiago Holanda de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The development of electrocatalysts for the oxidation of alcohols like methanol and ethanol is of great importance, once such alcohols can be used as fuel at the anode of fuel cells, devices that convert chemical energy into electrical energy. Thus, this work reports the synthesis of nanocatalysts of PdAu supported on carbon, physical characterization of materials prepared and the evaluation of the catalytic activity for the oxidation of methanol and ethanol. The physical characterization was performed using X-ray diffraction, transmission electron microscopy, Energy Dispersive spectroscopy X-Ray and X Ray Absorption Spectroscopy techniques. Materials were also electrochemically characterized by cyclic voltammetry. The catalytic activity of the prepared materials was studied using standard electrochemical techniques such as chronoamperometry and cyclic voltammetry and also the spectroelectrochemical technique of in situ FTIR, which allows the identification of reaction products and intermediates. With the X-ray diffraction was possible to prove the gold incorporation into the Pd structure for some materials. The transmission electron microscopy images showed a widening in the distribution of particle size with increasing the amount gold in the material, and a good dispersion of the nanoparticles on carbon support, except for pure Pd. The X-ray absorption spectra indicated a emptying on the 4d band of the material containing PdAu. Related to the catalytic activity for the electro-oxidation of ethanol and methanol, materials containing both palladium and gold showed better activity than pure Pd. The spectro-electrochemical data indicate acetate as main oxidation product for ethanol oxidation and formate for methanol oxidation.

O desenvolvimento de eletrocatalisadores para as reações de oxidação de álcoois como metanol e etanol é de grande importância, pois esses álcoois podem ser utilizados como combustíveis no ânodo das células a combustível, dispositivos que transformam energia química em energia elétrica. Neste sentido, este trabalho relata a síntese de nanocatalisadores de PdAu suportados em carbono, a caracterização física dos materiais preparados e a avaliação da atividade catalítica para a oxidação de metanol e etanol. A caracterização física foi realizada utilizando-se as técnicas de Difratometria de Raios X, Microscopia Eletrônica de Transmissão, Espectroscopia de Energia Dispersiva de Raios X e, Espectroscopia de Absorção de Raios X. Os materiais também foram caracterizados eletroquimicamente por voltametria cíclica. A atividade catalítica dos materiais preparados foi estudada através de técnicas eletroquímicas convencionais, como voltametria cíclica e cronoamperometria, e também da técnica espectro-eletroquímica de FTIR in situ, que permite a identificação de produtos e intermediários das reações. Com os difratogramas de Raios X foi possível comprovar a incorporação de ouro na estrutura do paládio para alguns materiais. As imagens de microscopia eletrônica de transmissão indicaram um alargamento na distribuição de tamanho das partículas à medida que aumenta a quantidade ouro e uma boa dispersão do material no carbono, exceto para Pd puro. Os espectros de absorção de raios X indicaram um esvaziamento da banda 4d do paládio nos materiais contendo ouro. Com relação à atividade catalítica para a eletro-oxidação de etanol e metanol, os materiais contendo paládio e ouro apresentaram atividade melhor que o Pd puro. Os dados espectro-eletroquímicos indicaram para etanol a presença de acetato e para metanol a presença de formiato.
Keywords: Físico-química; Eletrocatálise; Células à combustível; Eletroquimica; Nanopartículas; Nanoparticles